Determinants of Consumer Purchase Decision in Home Industry Product: A Case Study on Shrimp Cracker Home Industry - Arfamaini, Revi (Iqtishodia: Jurnal Ekonomi Syariah, 2023)
The development of the digital world today forces MSMEs to adapt in order to survive and thrive. Currently, many merchants complained that their sales had decreased, which resulted in a decrease in turnover. Therefore, MSMEs should be able to adapt by the digitalization of industry and trade. However, the current problems of MSMEs are not far away and still revolve around the same thing, namely capital. this study aims to investigate whether the variables of WoM, distribution channels, and product quality affect the decision to buy shrimp crackers and how these independent variables affect the dependent variable. This study is a quantitative study with multiple regression analysis. Based on data analysis and discussion this study found partially WoM (X1) influence purchase decision (Y) while product quality (X2) also influence purchase decision (Y) as well as distribution channels (X3) at shrimp cracker MSMEs at Tunjungan Village. Meanwhile, simultanousely all IV (X1, X2, and X3) are influence the DV (Y) with R2 about 0.661 or in other word 66.1% of DV are influenced by IVs.